Two new species of Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil and updated keys - Rapoza, Márcia; Waichert, Cecilia (European Journal of Taxonomy, 2022)
Ageniella Banks, 1912 is a paraphyletic group exclusive to the Nearctic and Neotropical regions. The genus has a remarkable morphological diversity among species and strong sexual dimorphism, hampering taxonomic studies of it. Herein, we add two new species to the Neotropical fauna of Ageniella: A. caerulea sp. nov. belonging to the subgenus Ameragenia and A. ruschi sp. nov. belonging to the subgenus Priophanes; both species are described and illustrated. A brief discussion of subgeneric characters and an updated taxonomic key to the species of Ageniella known from Brazil are provided.